2015
DOI: 10.1186/s12913-015-0947-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of appropriate healthcare technologies: a cross-sectional study in rural Zhejiang of China

Abstract: BackgroundAppropriate healthcare technologies (AHTs) are an important strategy for improving the availability and accessibility of healthcare services. It is not clear what impact AHTs have on health workers and consumers; and whether those AHTs can continue in place without special or ongoing financial support. This study investigated the attitudes of health workers and consumers towards AHTs.MethodsHealth facilities from five counties in Zhejiang were surveyed. Participants of the study included all health w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Sub-theme 1: Information on appropriate usage was mentioned by participants on the need for adequate information on appropriate usage of facilities and services as was quoted. This finding is consistent with Ren, Liu, Gao, et al (2015) study, which affirmed the use of appropriate healthcare technologies, the technologies could be information or other evidence-based approaches, in a cross-sectional study in rural Zhejiang of China. The findings demonstrate that appropriate health services information usage demonstrated that AHTs have been widely accepted by the target audience in China, on account of appropriate information on service usage.…”
Section: Discussionsupporting
confidence: 90%
“…Sub-theme 1: Information on appropriate usage was mentioned by participants on the need for adequate information on appropriate usage of facilities and services as was quoted. This finding is consistent with Ren, Liu, Gao, et al (2015) study, which affirmed the use of appropriate healthcare technologies, the technologies could be information or other evidence-based approaches, in a cross-sectional study in rural Zhejiang of China. The findings demonstrate that appropriate health services information usage demonstrated that AHTs have been widely accepted by the target audience in China, on account of appropriate information on service usage.…”
Section: Discussionsupporting
confidence: 90%
“…52,[104][105][106] However, running a successful NCD service in PHC needs skilled human resources, management systems, relevant medicines with an adequate supply, and appropriate equipment. [107][108][109] In LMICs, these are often limited due to financial considerations or a weak health infrastructure. 110,111 In PHC specifically, incorporating technologies into the services provided has the potential to accelerate PHC as the integrative hub for health care, supporting the efforts of patients, promoting collaboration with specialists, facilitating connections with nursing homes and home health, and advancing population health within a framework that improves the patient experience, quality, and value.…”
Section: Strengths Of Primary Health Carementioning
confidence: 99%
“…Based on this evidence, the EMHP has been scaled up to develop a mobile app to deliver Health EDRM-related messages to rural communities in China. The widespread prevalence of mobile technologies expands opportunities for Mobile Health (mHealth) for Health EDRM education initiatives, particularly in low- and middle-income countries and for people in remote villages or marginalised population groups [ 46 , 47 , 48 ].…”
Section: Recommendationsmentioning
confidence: 99%